Modern Approaches to Improving the Functional Properties of Canvas Fabrics (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
in this article, the research work was carried out in the enterprises of the cluster system of "ZAMIN ANGOR CLUSTER" LLC and "DENOV TEXTILE CLUSTER" LLC in Surkhandarya region. For him, the degree of contamination of the fiber of the seed obtained from promising selection varieties Surkhan-9, Surkhan-101, Termez-49, Termez-208 and Surkhan-102 grown in some farms of Denov and Shorchi districts was studied in the laboratory of the Department of "Textile materials Science".